Analisis Faktor Pendorong dan Penghambat Adopsi Aplikasi OVO di Kota Jambi: Pendekatan IPA dan UTAUT 2 - Setiawan, Dedy; Enggrani Fitri, Lucky (Jurnal Sistem Informasi Bisnis, 2025)
The purpose of this study is to analyze the interest and behavior of using OVO applications, as well as determine the importance rating using Importance Performance Analysis (IPA) of factors that influence interest and usage behavior based on the Unified Theory of Acceptance and Use of Technology 2 (UTAUT 2). The questionnaire was distributed to OVO users in Jambi Province with a total sample of 155 respondents. This study used non-probability sampling techniques, and the analysis method used was PLS-SEM with SmartPLS 3 software. The results showed that habits were the most influential and had the highest level of importance to the interest in using OVO in Jambi City. Meanwhile, for usage behavior, the factor that most influences it is supporting conditions, which have a high level of importance and performance according to the importance-performance map analysis (IPMA) felt by OVO users in Jambi Province. The results of this research provide valuable insights for companies or developers in decision-making related to product development, marketing strategies, and resource investment. They can allocate resources more effectively based on a better understanding user preferences and needs.